2015
DOI: 10.4028/www.scientific.net/ssp.237.41
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of CrN/CrCN Gradient Coatings

Abstract: The paper describes the optimization procedure supporting the designing process of geometry of gradient coatings basing on numerical simulation of internal stress and strain distributions in the coating and substrate. In mathematical model the gradient coating is represented by the so-called transition functions describing the change of physico-chemical parameters such as Young's modulus, Poisson's ratio, thermal expansion coefficient and the density as a function of the spatial variables. The object of optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Application of surface treatment technologies, as physical vapour deposition, has currently high development potential it area of methods for tool materials properties increase [13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Application of surface treatment technologies, as physical vapour deposition, has currently high development potential it area of methods for tool materials properties increase [13][14].…”
Section: Introductionmentioning
confidence: 99%
“…conflicting criteria, in another case, each component of the vector criterion may reach its minimum at a different value of the vector of decision variables. However, there exist methods to facilitate the evaluation of acceptable (non-dominated) solutions (Pareto-optimal solutions: the solutions for which improvement of one of the criteria is inextricably linked to the deterioration of the others) for minimizing all the criteria simultaneously [20,22,23,26].…”
Section: Resultsmentioning
confidence: 99%
“…[21]. In turn, in [22] was optimized the geometry of multilayer TiN /TiAlN deposited on the substrate HSS (High Speed Steel) previously coated with metallic chromium. The optimization process was carried using a computer model basing on FEM (Finite Element Method) implemented in COMSOL Multiphysics 4.4 and MATLAB.…”
Section: Introductionmentioning
confidence: 99%
“…For monolayer coatings deposited by PVD techniques, it is often observed that increasing the hardness of the coatings is accompanied by a simultaneous increase in the Young's modulus and decrease of their ductility (impact resistance), which leads to a reduction of coating's fracture toughness due to the reduction of their ability to dissipate mechanical energy (through plastic deformation). In order to limit these effects, for example, a more complex structure of the coating is used such as multilayer coatings and multi-module Cr/CrN (Marulanda et al, 2012;Polcar et al, 2009;Ratajski et al, 2015), CrN/CrCN (Gilewicz et al, 2015;Szparaga et al, 2015aSzparaga et al, , 2015b or gradient CrN/Cr(C)N coatings (Fuentesa et al, 2008;Ratajski and Szparaga, 2012;Szparaga et al, 2015c;Zhang et al, 2009). The such structure of coating increases the resistance to cracking and enhances the adhesion state, e.g., by reducing residual stresses in the coating.…”
Section: Introductionmentioning
confidence: 99%